A CD44-targeted Cu(ii) delivery 2D nanoplatform for sensitized disulfiram chemotherapy to triple-negative breast cancer. Issue 15 (1st April 2020) - Gao, Zhiguo; Li, Yaojia; Zhang, Yu; An, Peijing; Chen, Fanghui; Chen, Jian; You, Chaoqun; Wang, Zhifei; Sun, Baiwang
Abstract : 2D metal–organic frameworks deliver Cu(ii ) in a safe and regulated manner to sensitize disulfiram chemotherapy for triple-negative breast cancer. Abstract : Recent studies have suggested that the anticancer activity of disulfiram (DSF, an FDA-approved alcohol-abuse drug) is Cu-dependent. Low system toxicity and explicit pharmacokinetic characteristics of DSF necessitate safe and effective Cu supplementation in local lesion for further applications. Herein, we presented a new conceptual 'nanosized coordination transport' strategy of Cu(ii ) that was realized in porphyrin-based metal–organic frameworks, Sm-TCPP, with strong binding ability to Cu(ii ) due to their coordination interactions. Sm-TCPP(Cu) was coated by hyaluronic acid (HA) that termed by Sm-TCPP(Cu)@HA, acting as 'beneficial horse' to target the tumor-localized HA receptor (CD44), thus liberating Cu(ii ) ions in cellular overexpressed reductants. The CD44-mediated Cu(ii ) accumulation efficiency of Sm-TCPP(Cu)@HA was benchmarked in vitro and vivo against the free TCPP (Cu) via ICP-MS analysis. More importantly, the sensitization effects of Sm-TCPP(Cu)@HA on the anticancer activity of DSF were demonstrated in vivo and in vitro . This study offered a new class of targeted Cu supplements to sensitize DSF for the effective treatment of cancer and established a versatile methodology for constructing a safe and specific delivery of metal ions within living organisms.